The Level of Knowledge and Behavior of Implementing Health Protocols for Mothers of Toddler during Covid-19 Pandemic - Aben BYH Romana; Fransiskus Salesius Onggang; Gladur Blasius; Susana Emo (Eduvest - Journal of Universal Studies, 2023)
The low awareness of mothers about implementing health protocols will have an impact on toddlers. The incidence of COVID-19 at the Wuhan China children's hospital reached 10.6% in toddlers, in Indonesia it was 2.9%, in East Nusa Tenggara there were 858 toddlers and at the Sikumana Health Center in Kupang City in 2020 6 toddlers, and in 2021 it increased to 70 toddlers. The study aims to find out relationship between the level of knowledge and behavior in implementing health protocols for mothers under five in the working area of ​​the Sikumana Health Center, Kupang City. This type of research method is an analytical quantitative research approachCross sectional study and using a parametric test, namely the chi-square test. Results of study shows most of the level of knowledge and behavior in implementing health protocols for mothers under five is in the good category. Statistical test resultsshows a p value of 0.000 < Alpha 0.05 meaning that there is a significant correlation or relationship betweenthe level of knowledge and behavior of mothers with toddlers regarding the implementation of health protocols at posyandu, Oepura village, Sikumana health center, Kupang City. There is a relationshipbetweenthe level of knowledge and behavior of mothers with toddlers about implementing health protocolsin the working area of ​​the Sikumana health center, Kupang city. It is hoped that the knowledge of mothers under five about implementing health protocols will be well maintained and those who still have sufficient and insufficient knowledge need to be increased